Situation Report: Romania, 15 April 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Manescu's Visit to Prague Ends Lagging "Socialist Education" and New Decree on Rules of "Community Life" "Lenin and Contemporary Economics" (I) Inauguration of Bucharest's Otopeni International Airport